AAUP Policy Documents and Reports - American Association of University Professors ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This document presents a wide range of policy documents and reports determined by the American Association of University Professors. The areas of concern include academic freedom, tenure, due process, college and university government, collective representation, professional ethics, student rights and freedoms, college and university accreditation, research and teaching, and collateral benefits. The constitution of the Association is also included. (MJM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Policy; College Faculty; Organizational Development; Organizations (Groups); Policy Formation; Professors; American Association of University Professors